ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA GURU-GURU ‘‘IKHLAS’’ KUOK KABUPATEN KAMPAR - Ardiana Ardiana; Gimin Gimin; Hardisem Syaburs (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack:the research aimed to discover financial development of KPRI Teachers “Ikhlas”Kuok for the years2012-2016 using analiysis of liquidity, solvency and rentability. Where the research was conducted in the environment KPRI Teachers “Ikhlas” Kuok. The data collection techniques that used were documentatio and interview techniques. The data analysis techniques that used were liquidity, solvency and rentability calculation ratio and trend analysis.The results showed that: the liquidity rate as indicated by the current ratio is ina bad category. The solvency rate as indicated by the total debt to aset and total debt to equity ratio is in a good category. The protability rateas indicated by the retur on aset and retur on equity is in bad category whereas net profit margin is in less than good category. Trend analysis is good.Key Words: Analysis, Ratio, Trend